Socialization About Importance Save Since Early - Fany'mah, Haliza; Mufidah, Khazimatul (Kontribusia : Research Dissemination for Community Development, 2024)
Financial management is one of the important things that must be done, wrong One method manage Money in a way simple is with _ save. Save can started from an early age or elementary school children. The aim of socializing savings from an early age to students class 4 And 5. School Base 100 Gresik, Benjeng is For increase interest save students and implementing a frugal lifestyle in their daily lives. Method used consisting of coordination, media preparation, socialization. Apart from presenting the material, students are invited to play quizzes to train concentration related to the benefits of saving early, through method the as form saying Thank You And appreciation student giving a gift in the form of a piggy bank which can be useful in saving activities. Results from socialization is can grow interest save student, increase knowledge about save like meaning save, benefit save And method save and be able to implement savings habits for grade 4 and 5 students at SD 100 Gresik, Benjeng.